Enhancing Employee Net Promoter Score through Branding and Engagement: Evidence from a Manufacturing Firm in Indonesia - Rohana, Siti; Sapruwan, Muhamad (Talent: Journal of Economics and Business, 2025)
PT Indonesia Epson Industry faces the challenge of increasing employee loyalty and engagement to support the company's performance. Employee Branding and Employee Engagement are considered important factors in creating a positive work environment and increasing employees' Net Promoter Score (NPS). This study aims to explore the relationship between Employee Branding and Employee Engagement on employee NPS in PT. Indonesia Epson Industry, as well as providing strategic recommendations to improve company loyalty and performance. This study uses a quantitative approach with an explanatory design. The number of samples in this study was 150 respondents. Data analysis was carried out using multiple linear regression through SmartPLS software. The results show that Employee Branding has a significant influence on Employee Engagement  and employee NPS. In addition, Employee Engagement has also been proven to have a significant influence on NPS. The study found that an effective Employer Branding strategy and a high employee engagement rate can significantly increase an employee's NPS, which reflects their loyalty and desire to recommend the company as a place to work. Employee Branding and Employee Engagement play an important role in increasing employee NPS at PT. Indonesia Epson Industry. For this reason, companies are advised to strengthen these two strategies by improving internal communication, providing more transparent rewards, and creating an inclusive work environment that supports the career development of employees.